If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -14 = 16x + -34 Reorder the terms: -14 + 3x = 16x + -34 Reorder the terms: -14 + 3x = -34 + 16x Solving -14 + 3x = -34 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -14 + 3x + -16x = -34 + 16x + -16x Combine like terms: 3x + -16x = -13x -14 + -13x = -34 + 16x + -16x Combine like terms: 16x + -16x = 0 -14 + -13x = -34 + 0 -14 + -13x = -34 Add '14' to each side of the equation. -14 + 14 + -13x = -34 + 14 Combine like terms: -14 + 14 = 0 0 + -13x = -34 + 14 -13x = -34 + 14 Combine like terms: -34 + 14 = -20 -13x = -20 Divide each side by '-13'. x = 1.538461538 Simplifying x = 1.538461538
| -56-14n=-8(-6b+1) | | 3y-21x=15 | | 6x^5+15x^3+6x=0 | | 11m-30=36 | | 2X+3(x-4)=4(2+3) | | 7x+20=3x+48 | | -24=18+6x | | 5(2x+3)=(4x+1)-2(3x+2) | | 1+1/16= | | 2n^2-2n-5=0 | | 6(2x-1)=14x-48 | | 4a+2=5.2 | | 7y-6=-55 | | 9x-2+2x=6 | | 3r+4.5=12 | | 7x+20=3x-48 | | -y+3=10 | | 4x-8=-6 | | 5x+11=-73-9x | | 3d+5d+2= | | 10s-4=8 | | -104=8(r-8) | | .3-1.6=.625m | | -6d-6=12 | | 2(x+3)=10(2+4x) | | 17=z/3-21 | | (x-5)(2x+3)-2x(x+1)=0 | | 3x-5=4x+5-x | | -4(3k-8)=128 | | 3-4+11=2 | | 4n+20=2n-4 | | x-(-19)=23 |